Penerapan Metode Seleksi Maju dan Metode Penyisihan untuk Analisis Faktor Penentu Impor Beras BULOG di Sumatera Utara - Purba, Mutia Agustin; Siregar, Usnul Marisa; Sinaga, Roberto Karlos; Hasibuan, Febriyanti; Fitriyani; Chairunisah (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the factors that influence BULOG’S rice imports in North Sumatra using the forward selection and backward elimination. This research focuses on the factor that influence the amount of rice imports considering how important rice is as a staple food in Indonesia. The data used in this research is secondary data on rice imports in 2010-2020 provided by the North Sumatra Province Central Statistics Agency. The analysis findings show that, with a combined contribution of 96.5%, BULOG’S rice output and stocks are the main element that have a large impact on the volume of rice imports. This research provides an important contribution in formulating the dynamics of rice imports to North Sumatra which can serve as a guide for developing food security polices.